An Analyisis of Students' Ability in Writing Descriptive Text - Mufidatul Latifah; Dian Safitri (Universitas Negeri Padang, 2023)
English language learning is based on four pillars: speaking, reading, listening, and writing. Writing is vital to helping learners acquire language because it allows them to engage with words, phrases, and extended pieces of writing to express themselves clearly and to reinforce the grammar and vocabulary they are learning in class. However, the researcher discovered that several students at SMAN 2 Lubuk Sikaping committed a number of mistakes in writing text especially Descriptive Text especially in writing identification and description, and also using simple present tense. It was identified from their writing exercises. Thus the researcher analyzes the ability of the tenth grade students to write identification and description of descriptive text and also analyze the overall ability in writing descriptive text at SMA N 2 Lubuk Sikaping. This study has a descriptive quantitative research design. The category of the students’ ability in writing identification is “sufficient” with the mean was 2,35. Then, the category of the students’ ability in writing description is “sufficient” with the mean was 2,23. The overall ability of the students is categorized as “sufficient” with the mean is 2,35.